The Meaning of Dhikr According to Abdul Qadir Jaelani - Izzah Faizah Siti Rusydati Khaerani; Nandar Kusnandar; Solehudin Solehudin (Indonesian Journal of Islamic Studies, 2018)
This study examines the meaning of dhikr according to Abdul Qadir Al-Jailani as contained in Al-Jilani's. The choice of this figure was because his teachings were very closely related to the people in Indonesia, especially to the followers of the Naqshbandiyah Qadariyah Order. This research is a book research data processed through a method of description analysis in order to find a clear picture related to the meaning of dhikr in the literature. This study found: 1). The meaning of dzikir according to Abdul Qadir is to remember Allah in every moment of every event. In order to carry out what God commands and keep away from what God forbids and by doing the dhikr it will arrive at the mortal level. 2). The way of dhikr according to Abdul Qadir Jailani, there are two parts namely by oral and with qalb, for by oral that is by saying lafadz laa ilaha illaallah while with qalb must be done with: (a). Empty the heart other than the name of Allah (b). Get used to reading prayer beads at any time. (c). Don't concern yourself with worldly affairs but must always remember God (d). Trying to enjoy the dhikr so that it is truly enjoyable and feels mortality in his life. 3). The benefits of dzikir according to Abdul Qadir are: a). God also remembered, b). Forgiveness of sins, c). Up to mortal d). Enter the level of ma'rifaullah e). Calm his heart f). Meet with God g). granted the Prayer.